Analysis of miRNAs Involved in Mouse Heart Injury Upon Coxsackievirus A2 Infection - Wu, Zhaoke; Zhu, Shenshen; Qian, Juanfeng; Hu, Yanmin; Ji, Wangquan; Li, Dong; Zhu, Peiyu; Liang, Ruonan; Jin, Yuefei (Frontiers in Cellular and Infection Microbiology, 2022)
Coxsackievirus A2 (CVA2) has recently been constantly detected, and is associated with viral myocarditis in children. Our previous study demonstrated that CVA2 led to heart damage in a neonatal murine model. However, the molecular mechanism of heart injury caused by CVA2 remains largely unknown. Emerging evidence suggests the significant functions of miRNAs in Coxsackievirus infection. To investigate potential miRNAs involved in heart injury caused by CVA2, our study, for the first time, conducted a RNA-seq in vivo employing infected mice hearts. In total, 87, 101 and 76 differentially expressed miRNAs were identified at 3 days post infection (dpi), 7 dpi and 7 dpi vs 3 dpi. Importantly, above 3 comparison strategies shared 34 differentially expressed miRNAs. These results were confirmed by quantitative PCR (qPCR). Next, we did GO, KEGG, and miRNA-mRNA integrated analysis of differential miRNAs. The dual-luciferase reporter assay confirmed the miRNA-mRNA pairs. To further confirm the above enriched pathways and processes, we did Western blotting and immunofluorescence staining. Our results revealed that the predicted target genes were involved in diverse biological processes such as inflammatory responses, T cell activation, apoptosis, autophagy, antiviral immunity, and NK cell infiltration, and the disruption of tight junctions. The dysregulated miRNAs and pathways recognized in the current study can improve the understanding of the intricate interactions between CVA2 and the heart injury, opening a novel avenue for the future study of CVA2 pathogenesis.